Efficient and Mild Four-component Process for the Synthesis of Highly Substituted Dihydro-2-oxopyrroles using ZrOCl2∙8H2O as an Environmental-ly Friendly Catalyst - Mohamadpour, Farzaneh (UI Scholars Hub, 2020)
This study investigated the catalytic ability of ZrOCl2∙8H2O as a mild, environmentally benign nature, and economical catalyst for the multi-component efficient synthesis of biologically active highly substituted dihydro-2-oxopyrrole derivatives with excellent yields and short reaction times. This procedure has several advantages, including use of mild, nontoxic, and inexpensive catalysts, one-pot synthesis, environmentally benign nature, simple operational procedure, and highly efficient conditions.